2011
DOI: 10.1056/nejmsa1012065
|View full text |Cite
|
Sign up to set email alerts
|

The ClinicalTrials.gov Results Database — Update and Key Issues

Abstract: BACKGROUND-The ClinicalTrials.gov trial registry was expanded in 2008 to include a database for reporting summary results. We summarize the structure and contents of the results database, provide an update of relevant policies, and show how the data can be used to gain insight into the state of clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
611
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 654 publications
(629 citation statements)
references
References 20 publications
12
611
1
5
Order By: Relevance
“…Evaluating the enormity and complexity of the ClinicalTrials.gov dataClinicalTrials.gov datadatabase given its known limitations is certainly challenging [10][11][12], although the authors hope to have demonstrated its benefits, albeit after needing a highly time-consuming manual exercise to find the correct entries. Similar challenges have been reported by other authors examining the database in general [12][13][14][15][16]. Commentary…”
Section: Ind: Investigational New Drugmentioning
confidence: 99%
“…Evaluating the enormity and complexity of the ClinicalTrials.gov dataClinicalTrials.gov datadatabase given its known limitations is certainly challenging [10][11][12], although the authors hope to have demonstrated its benefits, albeit after needing a highly time-consuming manual exercise to find the correct entries. Similar challenges have been reported by other authors examining the database in general [12][13][14][15][16]. Commentary…”
Section: Ind: Investigational New Drugmentioning
confidence: 99%
“…More recently, Congress enacted within the FDA Amendments Act (FDAAA) of 2007 a provision (Section 801) that mandates the inclusion of "basic results" data from all clinical trials of approved drugs, biologics (other than phase 1 investigations), and devices (other than small feasibility studies) in the ClinicalTrials.gov database (19). Today, ClinicalTrials.gov contains basic results data for some clinical trials completed a er the enactment of FDAAA.…”
Section: Publication Biasmentioning
confidence: 99%
“…As recently as 2005 the world was still debating the 20 elements to be included in such protocol registrations and then quickly moved on to results posting (FDAAA 2007) [15,16] (update 2016 [17]). While we still have a way to go in making basic results and publications available [18,19], the current discussions described in the previous paragraph around individual patient data are part of a natural evolution in disclosure and transparency and not a sudden awakening. It is important to distinguish as well between 'transparency' and 'disclosure or access'.…”
Section: Introductionmentioning
confidence: 99%